Queen of the Nile - Maihack, Mike (2020)
"The time has come for Cleo to fulfill the ancient prophecy that declares her a savior and a hero, a prophecy she still struggles to accept. Cleo is joined by old and new friends as they fight to defend the galaxy she's come to call home against the evil Xaius Octavian. The Queen of the Nile must summon the strength to face down her enemy one last time, and keep both her friends - and herself - alive."--Page 4 of cover
Ages 8-12
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Juvenile fiction -- Comic books, strips, etc; Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Fiction; Cleopatra, -- Queen of Egypt, -- -30 B.C.; Time travel -- Juvenile fiction -- Comic books, strips, etc; Prophecy -- Juvenile fiction -- Comic books, strips, etc; Imaginary wars and battles -- Juvenile fiction -- Comic books, strips, etc; Good and evil -- Juvenile fiction -- Comic books, strips, etc; Time travel -- Fiction; Prophecies -- Fiction; Adventure and adventurers -- Fiction; Science fiction; Cartoons and comics; Prophecy; Imaginary wars and battles; Good and evil; Time travel; adventure story comics; Action and adventure comics; Comics (Graphic works); Graphic novels; Science fiction comics; Graphic novels; Science fiction comics; Action and adventure comics; Comics (Graphic works)